2022
DOI: 10.53771/ijstra.2022.3.2.0106
|View full text |Cite
|
Sign up to set email alerts
|

Design of automated power factor monitoring and repair tool for industry in real time based on Internet of Things

Abstract: The current electricity crisis is caused by the following things; The consumption of electrical energy continues to increase, the supply of electrical energy is limited, there is often a waste of electrical energy due to the use of electrical energy that should not be used (wasteful), as well as the need for electrical energy control that can control the electrical load remotely, and the power factor is lacking. Both resulting in reactive power losses and resulting in an increase in electric current which will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…In this test, to find out how long the time lag is between the user, the server, and the working prototype [13], [14]. In addition, this test aims to evaluate the server's response to 3, it can be concluded that there is a significant influence between Wi-Fi internet speed, user internet speed, and the delay that occurs.…”
Section: Results Data Transmissionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this test, to find out how long the time lag is between the user, the server, and the working prototype [13], [14]. In addition, this test aims to evaluate the server's response to 3, it can be concluded that there is a significant influence between Wi-Fi internet speed, user internet speed, and the delay that occurs.…”
Section: Results Data Transmissionmentioning
confidence: 99%
“…In the Wi-Fi internet speed range (0 -10 MBps) with the user internet speed range (0 -5 MBps), it can be seen that the delay that occurs is 1.5 seconds. In the Wi-Fi internet speed range (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) with the user's internet speed range (6 -10 MBps), the delay that occurs is 1 second. On the other hand, in the range of Wi-Fi internet speed (21 -30 MBps) and user internet speed range (6 -10 MBps), the delay that occurs is 0.8 seconds.…”
Section: Results Data Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research aims to design, manufacture, control, and evaluate a prototype that can make a system able to control electrical loads and can monitor in real time [4] and can even be controlled remotely using the internet. [5]The method used is through the Analysis, Design, Development, Implementation, Evaluation (ADDIE) approach, namely by studying the literature [6] to analyze the research object, then design and develop the design results and implement the design results and then implement them on the research object [7][8], all suggestions for improvement are used as an evaluation for improving this system [9]. The novelty of this research is to help users control and monitor electrical loads in real time and without the need to use applications or software that must be downloaded first [10], users only need to Entering the AdaFruit website is of course much easier and more flexible in use [11], unlike in previous studies that have been carried out, users must first download a software or application and this system is also equipped with the use of sensors so that this system can work with more ef isien [12].…”
Section: Fig 1 Electrical Capacity Datamentioning
confidence: 99%
“…Perbaikan faktor daya ini menggunakan kapasitor VAR [28]. Kapasitor untuk memperbaiki faktor daya dapat dilakukan dengan memparalelkan kapasitor VAR untuk memperbaiki faktor daya pada beban listrik [4], [42], [20].…”
Section: Segitiga Dayaunclassified